Baked bunnies, couple selfies, and video-call gardening: Visual communication in couple relationships during COVID-19 - Tarnutzer, Seraina; Lobinger, Katharina; Lucchesi, Federico (MedieKultur: Journal of media and communication research, 2023)
The emergence of the COVID-19 pandemic has had manifold societal implications. This paper reflects on the role of visual communication for maintaining relationship stability in couple relationships during the first wave of the pandemic, which we understand as a circumstantial turning point. The analysis is based on qualitative interviews with couples before, during, and after the first wave of COVID-19 in Switzerland, complemented by creative visual methods, follow-up surveys, and video calls. Our results show that visual practices are embedded in rather stable communication repertoires of couples during their relationship maintenance phase. Our study also points to the simultaneous use of a variety of visual practices, which led to a high “visual saturation”. These visual practices were found to contribute to relationship stability by reinforcing intimacy, a key factor in couple relationships, thereby shielding the relationships from circumstantial change.